2009
DOI: 10.1099/ijs.0.000463-0
|View full text |Cite
|
Sign up to set email alerts
|

Halorubrum chaoviator sp. nov., a haloarchaeon isolated from sea salt in Baja California, Mexico, Western Australia and Naxos, Greece

Abstract: Three halophilic isolates, strains Halo-G*T, AUS-1 and Naxos II, were compared. Halo-G* was isolated from an evaporitic salt crystal from Baja California, Mexico, whereas AUS-1 and Naxos II were isolated from salt pools in Western Australia and the Greek island of Naxos, respectively. Halo-G*T had been exposed previously to conditions of outer space and survived 2 weeks on the Biopan facility. Chemotaxonomic and molecular comparisons suggested high similarity between the three strains. Phylogenetic analysis ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…These values are within the range of values reported for Halogranum (Cui et al, 2010a) and Halorubrum Mancinelli et al, 2009) and higher than Hns. pteroides (58 mol%) (Burns et al, 2010), but lower than the value reported for Hbl.…”
Section: The Polar Lipids Of Strains Tbn21supporting
confidence: 88%
“…These values are within the range of values reported for Halogranum (Cui et al, 2010a) and Halorubrum Mancinelli et al, 2009) and higher than Hns. pteroides (58 mol%) (Burns et al, 2010), but lower than the value reported for Hbl.…”
Section: The Polar Lipids Of Strains Tbn21supporting
confidence: 88%
“…The major polar lipids are C 20 C 20 and sometimes C 20 C 25 Modern classification of the haloarchaea requires using phenotypic characterization, a chemotaxonomic approach based on the polar lipid composition as well as comparison of the 16S rRNA gene sequence, which is considered a universal phylogenetic and taxonomic molecular marker (Oren, 2012). The usefulness of this molecular marker, however, is questionable for haloarchaeal taxonomic studies as, over the years, studies have demonstrated that it has many qualities that make it difficult to distinguish species, such as: recombination between genera (Boucher et al, 2004;Papke et al, 2015) and closely related species (Papke et al, 2004(Papke et al, , 2007; that high sequence conservation does not discriminate between closely related species (Pesenti et al, 2008;Mancinelli et al, 2009); that their rRNA operons undergo intragenic recombination (Boucher et al, 2004); and that many genera (e.g. Haloarcula, Halosimplex and Halomicrobium) contain multiple gene copies with more than 5 % sequence divergence (Boucher et al, 2004).…”
Section: Two Extremely Halophilic Archaea Strains Cb34mentioning
confidence: 99%
“…Increasing loss of water due to vacuum exposure leads to partial denaturation of the DNA (64). The consequences are DNA strand breaks, which have been identified in cells of D. radiodurans and Halo-G, now identified as Halorubrum chaoviatoris (159), as well as in spores of B. subtilis, after exposure to space vacuum (55,56,158). Spores of the triple mutant repair-deficient strain TKJ 8431 (uvrA10 ssp-1 recA1) of B. subtilis, which are deficient in recombination repair, were the most sensitive specimens under conditions of space vacuum (115).…”
Section: ϫ5mentioning
confidence: 99%